2022
DOI: 10.3389/fninf.2022.871904
|View full text |Cite
|
Sign up to set email alerts
|

Time-Frequency Representations of Brain Oscillations: Which One Is Better?

Abstract: Brain oscillations are thought to subserve important functions by organizing the dynamical landscape of neural circuits. The expression of such oscillations in neural signals is usually evaluated using time-frequency representations (TFR), which resolve oscillatory processes in both time and frequency. While a vast number of methods exist to compute TFRs, there is often no objective criterion to decide which one is better. In feature-rich data, such as that recorded from the brain, sources of noise and unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Neural computations and information transmission in the brain are accompanied by oscillations ( Wang, 2010 ) embedded in rich time-frequency landscapes ( Moca et al, 2021 ; Bârzan et al, 2022 ). Oscillations often appear as events of finite duration and finite frequency span, called oscillation bursts or packets, intermixed with sustained oscillations and transient broadband events ( Tal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neural computations and information transmission in the brain are accompanied by oscillations ( Wang, 2010 ) embedded in rich time-frequency landscapes ( Moca et al, 2021 ; Bârzan et al, 2022 ). Oscillations often appear as events of finite duration and finite frequency span, called oscillation bursts or packets, intermixed with sustained oscillations and transient broadband events ( Tal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We did compare our approach with the wavelet features and found the latter to be somewhat inferior (see Inline Supplementary Figure 6). A more recent approach, termed superlets transform ( Moca et al, 2021 , Jorntell and Kesgin, 2023 ) has been shown to improve classification results by mitigating the time vs. frequency resolution problem ( Bârzan et al, 2022 ). However, a full comparison between different time–frequency features is out of the scope of this paper, as our main comparison between sliding-window and full-epoch decoding is performed at the raw data level.…”
Section: Methodsmentioning
confidence: 99%
“…Each subject's data were first transformed in the time-frequency domain from 1 to 43 Hz using the superlets algorithm [98] with a frequency resolution of 0.5 Hz. We selected the superlets algorithm over other more commonly used methods as it allows us to obtain a more optimal tradeoff between temporal and spectral resolution, and because it has been shown to yield better classification results compared to other approaches [99]. Before proceeding with any further analysis we trimmed 200 to 250 ms from the beginning and end of the epoched data in order to exclude any edge effects introduced by the time-frequency transform.…”
Section: Identification Of Channel-specific Beta Band and Burst Detec...mentioning
confidence: 99%